Renaissance posthumanism - Campana, Joseph; Maisano, Scott (Fordham University Press, 2016)
Renaissance Posthumanism brings together two historical periods--""Renaissance"" signifying a rebirth of the ancient and ""Posthumanism"" a death of the modern--to ponder each through the possibilities of the other. This collection rethinks the humanities under the auspices of the posthumanities of the posthumanities under the auspices of Renaissance humanism